2022
DOI: 10.3390/healthcare10050892
|View full text |Cite
|
Sign up to set email alerts
|

Impact of System and Diagnostic Errors on Medical Litigation Outcomes: Machine Learning-Based Prediction Models

Abstract: No prediction models using use conventional logistic models and machine learning exist for medical litigation outcomes involving medical doctors. Using a logistic model and three machine learning models, such as decision tree, random forest, and light-gradient boosting machine (LightGBM), we evaluated the prediction ability for litigation outcomes among medical litigation in Japan. The prediction model with LightGBM had a good predictive ability, with an area under the curve of 0.894 (95% CI; 0.893–0.895) in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Surgical specialties can, of course, cause diagnostic or medication related incidents as well. Nevertheless, a Japanese study [ 17 ] of machine learning-based prediction models for litigation outcomes found that 41.67% of all reported incidents occurred in an operation room. Procedures or surgeries were the most common reasons for litigation, with also the highest acceptance rate (56.1%).…”
Section: Discussionmentioning
confidence: 99%
“…Surgical specialties can, of course, cause diagnostic or medication related incidents as well. Nevertheless, a Japanese study [ 17 ] of machine learning-based prediction models for litigation outcomes found that 41.67% of all reported incidents occurred in an operation room. Procedures or surgeries were the most common reasons for litigation, with also the highest acceptance rate (56.1%).…”
Section: Discussionmentioning
confidence: 99%
“…We summarized the previous literature reports [14,[25][26][27][28][29][30][31], after fully understanding those common factors and considering the reality of medical malpractice cases in China, and divided the influencing factors on the degree of causality into medical factors (91 technical faults and 29 non-technical faults) and 10 patient factors (S1 Table ). Regarding the attribution of medical malpractice, it is generally observed that an increased number of affirmative responses in medical factors correlates with a higher degree of hospital liability in the case.…”
Section: Plos Onementioning
confidence: 99%
“…Machine learning plays a crucial part in the battle against various life-threatening diseases [ 5 , 6 , 7 ]. It also contributes significantly to educational and clinical studies [ 8 , 9 , 10 , 11 ]. Machine learning has shown significant potential in medical, engineering, psychology, multi-disciplinary science, earth sciences, analytical practices, healthcare, and other domains.…”
Section: Introductionmentioning
confidence: 99%